ASETKU: PENGEMBANGAN SISTEM INFORMASI MANAJEMEN INVENTARIS ASET BERBASIS WEB DAN QR CODE PADA INSTANSI PEMERINTAH DAERAH - abd halim (Pusat Penelitian dan Pengabdian Politeknik Negeri Tanah Laut, 2026)
The management of regional government asset inventories in public institutions generally still relies on conventional methods based on physical documents and spreadsheets, which are prone to recording errors and make it difficult to track asset holders in real-time. This study aims to design and implement AsetKu, a web-based asset inventory management information system specifically developed for the Library and Archives Office of Tanah Bumbu Regency, using QR Code technology as a physical asset identification mechanism. The system was developed using the prototyping method with a technology stack comprising PHP, MySQL, HTML5, CSS3 (Bootstrap 5.3), and JavaScript with a Progressive Web App (PWA) architecture. Evaluation was conducted through black-box testing of 24 test scenarios and usability testing using the System Usability Scale (SUS) questionnaire with 20 users. Functional testing results showed a success rate of 95.83%, while the average SUS score obtained was 82.5 (Excellent category). AsetKu is designed to simultaneously combine QR Code identification, PWA offline mode, and four-tier RBAC access control in a single integrated platform. This research makes an original contribution to the development of QR Code-based e-government solutions for regional government institutions with limited network infrastructure.